Chemical Composition of Skins and its Influence on Changes in Raw Materials during their Storage - Obidjon qizi, Rasulova Mamurakhon; Mamadalievich, Nazarov Otabek; Sheraliyevna, Amirova Toyiraxon (RA Journal of Applied Research, 2022)
The amount of minerals (ash) in the skin is small. These are mainly potassium and sodium salts (up to 0.4%), as well as small amounts (0.002-0.01%) of iron, copper, phosphorus, calcium, aluminum, etc. Potassium and sodium ions enter the skin with blood and lymph, iron ions - from blood hemoglobin, phosphorus is found in phospholipids, copper in the pigment, silicon, arsenic, calcium and magnesium in the epidermal layer.